Advancing sustainable innovations for a food secure future in India: Major impacts of the Cereal Systems Initiative for South Asia - Cereal Systems Initiative for South Asia (International Maize and Wheat Improvement Center, 2015)
The Cereal Systems Initiative for South Asia (CSISA) works to reduce hunger and increase food and income security of resourcepoor farm families in South Asia through the development and inclusive adoption of new cereal varieties, sustainable agricultural technologies and policies.